(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sjafaraenan, Umar MR, Herwin, Islamiyati A, Tuwo M, Zulkifli A. 2022. Nutritional potential of Semelesp. shellfish on estrogen levels and follicle stimulating hormone receptor genes in perimenopausal women. Biodiversitas 23: 1196-1203. The Bonea villagecommunity that often consume shellfish usually have a high libido and experience menopause abovethe age of 50 years.Therefore, this study aims to determinethe nutritional potential of Semele sp.on the Follicle-Stimulating Hormone Receptor (FSH-R) gene in perimenopausal womenas well asthe levels of estrogen and polymorphisms.The experimental method with a one-group preandpost-test design was used by measuring 10 perimenopausal women respondents aged 40-45 before and after consuming Semele sp. 2 times a week for 2 months. Furthermore, blood samples were collected through the median cubital vein 2-3 mL before and after the treatment, The nutritional measurement of Semele sp. including protein was carried out using the Kjeldhal method, carbohydrates using the Anthrone method, and fat using the gravimetry. Also, the mineral content was determined using Atomic Absorption Spectrophotometry(AAS), while the estrogen levels were assessed with the ELISA technique. The FSH gene was examined using DNA extraction and amplification, electrophoresis, as well as Restriction Fragment Length Polymorphism (RFLP) with the Bsrl enzyme, while thet-test was conducted to examinethe effect of shellfish consumption. The results showed that the consumption of Semele sp.increased estrogen levels significantly, as the Asn680Ser, Asn680Asn, and Ser680Se genotypes were found in each respondent with the FSH-R gene. Based on the results,it was concluded that the regular consumption of Semele sp. increases estrogen levels and is applicable as analternative treatment to delay the incidence of menopause.